Factors associated with utilisation of university health centre services by students - Alkhawaldeh, Abdullah (International Journal Of Community Medicine And Public Health, 2017)
Background: Little is known about the factors that are associated with students’ utilisation of university health centre services. The current study examines factors associated with utilisation of university health centre services by students. Methods: Data were collected from 440 university students using a cross-sectional study design and self-reported questionnaire. Results: University health centre services were utilised by 147 (39.5%) of the students in the past 6 months. Utilisation of university health centre services was associated with gender, faculty, tobacco use and chronic illnesses. The main predictor of university health centre services utilisation at 6 months was chronic illnesses (OR=4.205). Conclusions: Although several factors were associated with university health centre services utilisation, chronic illness was the most important predictor.